2020
DOI: 10.12785/ijcds/090415
|View full text |Cite
|
Sign up to set email alerts
|

A New Hybrid Image Segmentation Method Based on Fuzzy C-Mean and Modified Bat Algorithm

Abstract: Magnetic resonance imaging (MRI) plays an important role in clinical diagnosis, because of that it has attracted increasing attention in recent years. The symptom of many diseases corresponds to the brain's structural variants. The detection of various diseases has became very useful through the segmentation methods. Fuzzy c-means (FCM) considers among the popular clustering algorithms for medical image segmentation. However, FCM is sensitive to the noise and falls into local optimal solution easily because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For healthy brain tissue segmentation, the performance of hybrid metaheuristic MOPSO and fuzzy clustering region-based active contours was found to be better than that of the others for both Dice score and sensitivity, as stated by Pham et al [51]. Boulanouar and Lamiche [53] reported that good results were obtained for both GM and WM segmentation using the Brainweb dataset. For segmentation of the hippocampus structure in the brain, the performance of hybridized deep learning based on 3D U-net with CRF was found to be better than that of the other methods as measured using the Dice score by Jiang and Guo [62].…”
Section: Trends In the Segmentation Methodsmentioning
confidence: 75%
See 2 more Smart Citations
“…For healthy brain tissue segmentation, the performance of hybrid metaheuristic MOPSO and fuzzy clustering region-based active contours was found to be better than that of the others for both Dice score and sensitivity, as stated by Pham et al [51]. Boulanouar and Lamiche [53] reported that good results were obtained for both GM and WM segmentation using the Brainweb dataset. For segmentation of the hippocampus structure in the brain, the performance of hybridized deep learning based on 3D U-net with CRF was found to be better than that of the other methods as measured using the Dice score by Jiang and Guo [62].…”
Section: Trends In the Segmentation Methodsmentioning
confidence: 75%
“…Additionally, this type of hybridized approach is generally used to solve or reduce the major drawbacks of machine learning segmentation methods, such as the possibility of being trapped in a local minimum and sensitivity to noise. Several studies [50][51][52][53][54][55] have employed a combination of metaheuristic and machine learning methods.…”
Section: Metaheuristic and Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Another domain where using BA shows its superiority is image and signal processing, in which the algorithm solves image segmentation [ 28 , 35 , 45 , 77 , 78 , 196 , 204 , 221 , 229 , 255 , 322 , 323 , 327 , 328 ], face recognition and fingerprint identification [ 23 , 44 , 80 , 230 ], magnetic resonance (MR) brain tumour classification [ 151 153 , 271 ], multilevel image thresholding [ 79 , 207 , 254 ], and signal processing application [ 5 , 161 , 302 ]. Figure 19 plots the applications of BA in image and signal processing domain.…”
Section: Applications Of Bat-inspired Algorithmmentioning
confidence: 99%
“…When tested on breast cytology images, the hybrid method, FCMGWO, demonstrated superior performance over the standard FCM, particularly in less detailed images. In [30,31], a new approach is developed to calculate the optimal initial values of clusters centroids based on a novel fitness function. The authors introduce a hybrid MRI segmentation method, MFBAFCM, combining the modified fuzzy bat algorithm (MFBA) and Fuzzy c-means (FCM).…”
Section: Introductionmentioning
confidence: 99%